2020
DOI: 10.1097/j.jcrs.0000000000000015
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of visual acuity and complications between primary IOL implantation and aphakia in patients with congenital cataract younger than 2 years: a meta-analysis

Abstract: To analyze the visual acuity and complications between primary intraocular lens (IOL) implantation and contact lens wearing, this literature search was performed with data on patients with congenital cataract younger than 2 years published in March 2019. Seven identified studies enrolling 675 eyes were selected for analysis. Patients with primary IOL implantation owned better visual acuity than those with aphakia who wore the contact lens (weighted mean difference = 0.161; 95% CI, 0.108-0.214). For visual axis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 42 publications
0
21
1
Order By: Relevance
“…There are also concerns about significant refractive errors resulting from the unpredictable ocular growth. 8 9…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are also concerns about significant refractive errors resulting from the unpredictable ocular growth. 8 9…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that patients with primary implantation owned better VA than those with aphakia but without significant statistical difference. 8 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Primary IOL implantation is usually performed in children older than 2 years of age. However, IOL implantation in children younger than 2 years of age remains a matter of controversy, despite the increasing evidence of safety for the procedure (16). IOL implantation before 7 months of age is considered at high risk of severe postoperative complications, as inflammation, PCO (Figure 1E) and glaucoma, particularly in bilateral cases (17)(18)(19).…”
Section: Cataract Diagnosis and Managementmentioning
confidence: 99%
“…The prevalence of glaucoma and strabismus was similar between the groups. Authors suggested that cataract surgery in children younger than 2 years should include primary IOL implantation, associated with optic capture or bag-in-the-lens IOL implantation techniques to reduce PCO incidence (16). However, when cataract is associated with others ocular conditions as microphthalmia, IOL implantation should be delayed (21).…”
Section: Cataract Diagnosis and Managementmentioning
confidence: 99%